Penguatan UMKM Desa Berbasis Produk Halal Menuju Desa Mandiri dan Berdampak - Muhammad Nur Abdi; Mukminati; Muryani Arsal; Naidah; Saida Said (Jurnal Dharma Bhakti Ekuitas, 2026)
This Community Service (PKM) activity was carried out by the Faculty of Economics and Business, Muhammadiyah University of Makassar, at the Balla Barakkaka Ri Galesong Traditional House, Takalar Regency, on October 5–7, 2025. This program aims to increase the capacity and economic independence of village communities by strengthening micro, small, and medium enterprises (MSMEs) based on halal products by utilizing local potential. This activity uses a participatory approach with various methods, including group workshops, Islamic financial literacy training, mapping local economic potential, designing product designs and packaging, and ongoing mentoring. Through collaboration with BTN Syariah and the lecturers of the Faculty of Economics and Business, Muhammadiyah University of Makassar, the community gained an increased understanding of halal principles, access to Islamic capital, and a profit-sharing system without usury. The results of the activity showed a significant increase in Islamic financial literacy, awareness of halal certification, and the competitiveness of local MSMEs. A total of 12 superior village products were proposed for halal certification. In addition, this activity had a positive impact on increasing community income, empowering women and youth, and strengthening local cultural identity. This program is a model for sustainable local economic empowerment and supports the vision of “Independent and Impactful Villages” as a concrete manifestation of higher education’s contribution to community development based on Islamic values ​​and sharia economics. Keywords: community empowerment, MSMEs, halal products, islamic financial literacy, local potential. Abstrak Kegiatan Pengabdian Kepada Masyarakat (PKM) ini dilaksanakan oleh Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Makassar di Rumah Adat Balla Barakkaka Ri Galesong, Kabupaten Takalar, pada tanggal 5–7 Oktober 2025. Program ini bertujuan untuk meningkatkan kapasitas dan kemandirian ekonomi masyarakat desa melalui penguatan usaha mikro, kecil, dan menengah (UMKM) berbasis produk halal dengan memanfaatkan potensi lokal. Kegiatan ini menggunakan pendekatan partisipatif dengan berbagai metode, meliputi workshop kelompok, pelatihan literasi keuangan syariah, pemetaan potensi ekonomi lokal, perancangan desain dan kemasan produk, serta pendampingan berkelanjutan. Melalui kolaborasi dengan BTN Syariah dan dosen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Makassar, masyarakat memperoleh peningkatan pemahaman mengenai prinsip halal, akses permodalan syariah, dan sistem bagi hasil tanpa riba. Hasil kegiatan menunjukkan peningkatan signifikan dalam literasi keuangan syariah, kesadaran sertifikasi halal, serta daya saing UMKM lokal. Sebanyak 12 produk unggulan desa diusulkan untuk memperoleh sertifikasi halal. Selain itu, kegiatan ini berdampak positif terhadap peningkatan pendapatan masyarakat, pemberdayaan perempuan dan pemuda, serta penguatan identitas budaya lokal. Program ini menjadi model pemberdayaan ekonomi lokal yang berkelanjutan dan mendukung visi “Desa Mandiri dan Berdampak” sebagai wujud nyata kontribusi perguruan tinggi terhadap pembangunan masyarakat berbasis nilai-nilai Islam dan ekonomi syariah. Kata kunci: pemberdayaan masyarakat, UMKM, produk halal, literasi keuangan syariah, potensi lokal.